An Analysis Of Proficiency And Motivation On The Choices Of English Language Learning Strategies Of Smk Negeri 1 Bmr - Iluh karina; Hadziq Fikri, Arief; Zulaikah; Rohmah, Ainur (English Education Program, Education Faculty, Universitas Nurul Huda, 2023)
The objectives of this investigation were twofold: 1) to identify language learning strategies commonly used by tenth graders at SMK Negeri 1 Belitang Madang Raya , and 2) to determine the roles of three variables contributing to their strategy use: language proficiency and motivation. A set of questionnaires consisting of the Strategy Inventory for Language Learning (SILL), and the Motivated Strategies for Learning Questionnaire. This study was a qualitative study using Descritive method. The population in this study were all tenth graders at SMK Negeri 1 Belitang Madang Raya for the academic year 2021/2022 with a total of 159 students from five classes. The writer using random sampling technique to take samples. The sampling technique was carried out in one class, namely (TKJ1) which consisted of 30 students. the writer found that memory strategies 228(76%) ,Cognitif strategies 59(20%), Compensation strategies 180(60%), Metacognitive 105(35%), Affective Strategies 160(53%), Social Strategies 200(67%), The analysis revealed that, in general, memory strategies were found to be the most common learning strategies, whereas Cognitive strategies were the least common. Motivation was reported to be the most significant variables affecting their choices of language learning strategies. The analysis revealed certain elucidating facts that can be utilized in future planning of English language teaching to improve the English performance of students SMK Negeri 1 Belitang Madang Raya. Keyword: Learning Strategies, Proficiency And Motivation